2017
DOI: 10.5194/bg-14-2283-2017
|View full text |Cite
|
Sign up to set email alerts
|

The origin of methane in the East Siberian Arctic Shelf unraveled with triple isotope analysis

Abstract: Abstract. The Arctic Ocean, especially the East Siberian Arctic Shelf (ESAS), has been proposed as a significant source of methane that might play an increasingly important role in the future. However, the underlying processes of formation, removal and transport associated with such emissions are to date strongly debated. CH4 concentration and triple isotope composition were analyzed on gas extracted from sediment and water sampled at numerous locations on the shallow ESAS from 2007 to 2013. We find high conce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 67 publications
2
54
0
1
Order By: Relevance
“…Near the shore, methane concentrations were slightly higher in 2013, but there was no significant difference overall (Wilcoxon signed-rank test for paired data; n = 18, p = 0.84). In the same study area and in the summer of 2014, other authors reported a range of 10 to 100 nmol L −1 (Sapart et al (2017), as estimated from Fig. 2 of that paper).…”
Section: Methane Concentrationssupporting
confidence: 53%
See 1 more Smart Citation
“…Near the shore, methane concentrations were slightly higher in 2013, but there was no significant difference overall (Wilcoxon signed-rank test for paired data; n = 18, p = 0.84). In the same study area and in the summer of 2014, other authors reported a range of 10 to 100 nmol L −1 (Sapart et al (2017), as estimated from Fig. 2 of that paper).…”
Section: Methane Concentrationssupporting
confidence: 53%
“…Ebullition of methane from the sediment in this area is also reported, resulting in methane fluxes that are 1-2 orders of magnitude higher than the calculated values (Table 5). Previous examinations of methane released by ebullition did not find any isotopic evidence of oxidation; thus, this methane will almost exclusively be released into the atmosphere (Sapart et al, 2017). However, whether this ebullition really results in elevated atmospheric methane concentrations remains a matter of debate, as this fingerprint has not been detected by others Berchet et al, 2015).…”
Section: Diffusive Methane Fluxmentioning
confidence: 93%
“…There are also other minor natural CH 4 sources, such as ocean, geological seepages, subsea permafrost, and sea ice, in the Arctic region, of which isotopic signatures are close to the values of wetlands and/or fossil fuel sources (e.g., Sapart et al, ; Walter Anthony et al, ). As mentioned above, the backward trajectory analysis indicates that Churchill is strongly influenced by air masses from the HBL and its surroundings in summer.…”
Section: Resultsmentioning
confidence: 98%
“…Thawing of subsea permafrost on the East Siberian Arctic Shelf (ESAS) has also been suggested to enhance CH 4 release to the atmosphere (Sapart et al, ; Shakhova et al, ; Shakhova, Semiletov, Leifer, et al, ). However, this conflicts with findings that subsea permafrost cores can contain insufficient CH 4 to fuel the fluxes reported (Overduin et al, ; Shakhova, Semiletov, Salyuk, et al, ; Thornton, Geibel, et al, ).…”
Section: Marine and Freshwater Systemsmentioning
confidence: 99%